Conversations with Marilia Muylaert: caring for yourself in times of crisis - Rodrigues, Camila Cristiana de Oliveira [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2022)
The present interview was the way found to give written expressiveness to the narrative presented by Dra. Marilia Muylaert at the event Conversations in Schizoanalysis: self-care in times of crisis. In this interview, Dra. Marilia presents us with her latest reflections on one of the most relevant themes of our time: thinking about the crisis in the Brazilian context from the ethical-aesthetic-political paradigm. The interviewee dialogues with authors such as Foucault, Nietzsche and Deleuze, and the notion of self-care was chosen as the main device to develop a kind of cartography of the current crisis. In addition, notions such as ethics, the potency of life and trust are recovered throughout this conversation with the aim of directing thought towards an active project for the future.
Keywords: Crisis; Take Care of Yourself; Difference Philosophy